Anurocampa (Lepidoptera: Notodontidae): two new species, systematics and immature stages - Orlandin, Elton; Laurent, Ryan A. St; Piovesan, Mônica; Hallwachs, Winnie; Chacón, Isidro; Janzen, Daniel; Carneiro, Eduardo (Zootaxa, 2023)
Notodontidae (Lepidoptera, Noctuoidea) comprise over 4,000 described species distributed worldwide, among which nearly half are restricted to the Neotropics. Morphology of adults and immatures of Notodontidae have been broadly investigated and many larval, pupal, and adult characters were found to be synapomorphies of subfamilies and tribes. Despite this, the current classification of Notodontidae remains unsettled as most recent classification systems are contradictory due to reliance on incomplete global sampling and, many taxa, especially in the Neotropics, are still informally classified as incertae sedis. Anurocampa Herrich-Shäffer was recently treated as an incertae sedis genus, and immature and adult characters may provide further evidence for its systematic position among the Notodontidae. With this goal in mind, the present study describes the immature stages of Anurocampa mingens Herrich-Shäffer from Brazil and describes two new species in the genus from Costa Rica based on morphology and mitochondrial DNA: Anurocampa markhastingsi Chacón and St Laurent sp. nov. and Anurocampa abelardochaconi Chacón and St Laurent sp. nov. and discusses the systematic position of Anurocampa.